Diallel Analysis of Chili Pepper Resistance to Melon Aphid (Aphis gossypii Glover) Infestation in Seedling Phase - Ady Daryanto; Muhamad Syukur; Awang Maharijaya; Purnama Hidayat (Universitas Sembilanbelas November Kolaka, 2018)
Aphis gossypii Glover is one of important insect pest in Indonesia. Genetic analysis of resistance to A. gossypii is required in plant breeding program to obtain host-plant resistance cultivar. Diallel analysis was used to estimate genetic parameters for chili pepper resistance to A. gossypii infestation in early generation. The objective of this research was to estimate genetic parameters of chili pepper resistance to A. gossypii infestation with diallel crossing design. The F1 and parent plants were arranged in randomized competed block design with three replication. Resistance lines was measured using choice test laboratory screening techniques. Two aphids were infested per plant and stopped 12 days after first infestation. Different lines respond was detected as shown by significant numbers of aphid per leaf, total aphid per plant, and total winged aphid per plant. There were no maternal effect and resistance were controlled by recessive and polygenic genes. Gene effects for resistance to aphid’s infestation were additive and dominance. Dominance effect larger than additive effects. Broad-sense heritability values were high but narrow-sense heritability values were very low